Evaluation of a pictorial method to obtain subject‐specific inertial properties in equine limb segments - Nauwelaerts, Sandra; Clayton, Hilary M. (Journal of morphology (1931), 2018)
Data describing segmental masses and moments of inertia (MOI) of limb segments are required for inverse dynamic calculations. In horses, these values are usually calculated using regression equations that have been developed from a limited number of horses representing a small number of breeds. The objective of the present study was to evaluate the performance of a scaling method and a pictorial method for estimating of the values of segmental masses, lengths, and MOI in the equine limb segments by comparing their output with the standard technique involving direct measurements. Limbs of 30 horses of various breeds and sizes were disarticulated post mortem. Segmental masses, lengths, and MOI were determined using a standard method based on weighing the segments, measuring their length with calipers, and estimating the MOI from the rotational frequency of a trifilar pendulum. The scaling method used a jack‐knifing procedure to avoid the need for two data sets. The pictorial method was based on digitization of two orthogonal photographs to determine segmental volumes, which were combined with published values for average segment densities to determine the inertial parameters. Scaling method and pictorial method provided comparable estimation of segmental messes and lengths, but the scaling method performed better in estimating segmental MOI. The scaling method worked well enough in the majority of horses but there were a few horses in which it was less effective. The pictorial method sometimes showed a bias correctable by regression equations but it may not warrant the additional effort unless for specific cases. A scaling method based on a jackknifing procedure and a pictorial method based on digitizing two orthogonal photographs provide estimations of limb segmental masses and lengths that are comparable with those derived from regression equations.